High Preoperative Systemic Immune-Inflammation Index Values Significantly Predicted Poor Outcomes After on-Pump Coronary Artery Bypass Surgery - Parmana IMA; Boom CE; Poernomo H; Gani C; Nugroho B; Cintyandy R; Sanjaya L; Hadinata Y; Parna DR; Yulia M; Hanafy DA (Dove Medical Press, 2024)
I Made Adi Parmana,1 Cindy Elfira Boom,1 Herdono Poernomo,1 Chairil Gani,1 Budi Nugroho,1 Riza Cintyandy,1 Lisa Sanjaya,1 Yudi Hadinata,1 Dian Raseka Parna,1 Mefri Yulia,1 Dudy Arman Hanafy2 1Department of Anesthesiology and Intensive Care, National Cardiovascular Center Harapan Kita, Jakarta, Indonesia; 2Department of Cardiothoracic and Vascular Surgery, National Cardiovascular Center Harapan Kita, Jakarta, IndonesiaCorrespondence: I Made Adi Parmana, Department of Anesthesiology and Intensive Care, National Cardiovascular Center Harapan Kita, Jakarta, Indonesia, Email adiparmana13@gmail.comPurpose: On-pump coronary artery bypass grafting (CABG) is one of the most common revascularization surgical therapies for coronary artery disease (CAD). However, owing to the use of cardiopulmonary bypass ("on-pump"), the body develops systemic inflammatory response syndrome, which leads to the risk of morbidity and mortality. This study aimed to determine the perioperative outcomes of patients who underwent on-pump CABG surgery using the systemic immune-inflammation index (SII).Patients and methods: This single-center retrospective study used secondary data from patients' electronic medical records and medical records archives at the National Cardiovascular Center Harapan Kita, who underwent on-pump CABG from January 2019 to December 2022. A total of 1056 on-pump CABG procedures were performed after exclusion. Lymphocyte, segmental neutrophil, and platelet counts from the preoperative data were used to calculate the SII values. An SII cutoff value of 528.715 × 103/mm3 divided the patients into two groups.Results: The SII value of 1056 patients were calculated, among which 490 (46%) patients had a preoperative SII value of ≥ 528.715 × 103/mm3. Multivariate analysis showed that a high SII significantly prolonged the duration of surgery (OR 1.005, 95% CI 1.003- 1.006) and cardiopulmonary bypass (CPB) time (OR 1.007, 95% CI 1.005- 1.009). High SII values significantly predicted prolonged mechanical ventilation (OR 6.154, 95% CL 3.938- 9.617), intensive care unit (ICU) stay (OR 6.332, 95% CL 4.232- 9.474), and hospital stay (OR 3.517, 95% CL 2.711- 4.562). Regarding other perioperative outcomes, a high SII significantly predicted the risk of postoperative atrial AF, cardiac arrest, acute myocardial infarction, and mortality.Conclusion: A high preoperative SII value can predict morbidity and mortality in patients undergoing on-pump CABG surgery.Keywords: systemic immune-inflammation index, on-pump coronary artery bypass graft, systemic inflammation, morbidity, mortality